Atezolizumab Monotherapy Window Preceding Combined Neoadjuvant Chemotherapy and Immune Therapy in Triple-Negative Breast Cancer-The neoMono Trial - Kolberg, Hans Christian; Schumacher, Johannes; Erber, Ramona; Braun, Michael; Fasching, Peter; Grischke, Eva Maria; Schem, Christian; Lux, Michael P.; Deryal, Mustafa; Hoffmann, Oliver; Heinrich, Bernhard; Kunz, Georg; et al. (Clinical Cancer Research, 2025)
PURPOSE: Exploratory data suggest a benefit of an immune checkpoint inhibitor (ICI) monotherapy window in early triple-negative breast cancer (TNBC). The neoMono trial prospectively investigated whether the addition of an atezolizumab monotherapy window before neoadjuvant atezolizumab and chemotherapy improves pathologic complete remission (pCR) rates in early TNBC. PATIENTS AND METHODS: neoMono is a phase 2 randomized multicenter trial that recruited patients with primary TNBC larger than 10 mm. Neoadjuvant treatment in both arms consisted of neoadjuvant atezolizumab and chemotherapy, with treatment in arm A preceded by atezolizumab monotherapy 2 weeks before combination therapy. This study used a Bayesian trial design. RESULTS: A total of 359 patients were included. Overall, pCR rates in study arms A and B were similar (intention-to-treat population: 65.7% and 69.0%, respectively). In an exploratory analysis, pCR rates in PD-L1-positive tumors were 91.5% in arm A and 82.2% in arm B. The corresponding pCR rates in the PD-L1-negative group were 56.1% in arm A and 64.5% in arm B. In patients with low-risk TNBC (cT1c and cN0), pCR rates in the PD-L1-positive group were 100.0% in arm A and 90.0% in arm B, and the corresponding pCR rates in the PD-L1 (immune cell)-negative group were 65.9% and 76.3%, respectively. CONCLUSIONS: The neoMono trial demonstrated the highest pCR rates reported in a phase II/III trial in TNBC, particularly in the case of PD-L1 positivity. Although no significant impact of an ICI monotherapy window on the pCR rate in the unselected intention-to-treat population could be demonstrated, our data reinforce the use of combinations of neoadjuvant chemotherapy and ICI in this indication.
CRIS-Team Scopus Importer:2025-11-28